Steps towards implementation of protocolized dose reduction of adalimumab, etanercept and ustekinumab for psoriasis in daily practice - L.S. van der Schoot; J.J. Janssen; M.T. Bastiaens; A. de Boer-Brand; C. Christiaansen-Smit; D.N.H. Enomoto; R. Hovingh; R.A. Tupker; M.M.B. Seyger; L.M. Verhoef; J.M.P.A. van den Reek; E.M.G.J. de Jong (Taylor & Francis Group, 2023)
Background Dose reduction (DR) of adalimumab, etanercept and ustekinumab has proven to be (cost-)effective in psoriasis patients with low disease activity. Further implementation is needed to establish application of DR for eligible patients. Objectives To evaluate the implementation of protocolized biologic DR in daily practice. Methods A pilot implementation study was performed in 3 hospitals during 6 months. By combining education and protocol development, involved healthcare providers (HCPs) were directed toward the adoption of protocolized DR. DR of adalimumab, etanercept, and ustekinumab was achieved by stepwise injection interval prolongation. Implementation outcomes (fidelity, feasibility) were assessed. Factors for optimizing implementation were explored in interviews with HCPs. Uptake was measured in patients by chart review. Results The implementation strategy was executed as planned. Implementation fidelity was less than 100% as not all provided tools were used across study sites. HCPs indicated the feasibility of implementing protocolized DR, although time investment was needed. Identified additional factors for successful implementation included support for patients, uptake of DR into guidelines, and supportive electronic health record systems. During the 6 months intervention period, 52 patients were eligible for DR of whom 26 (50%) started DR. The proposed DR protocol was followed in 22/26 patients (85%) on DR. Conclusion Additional staff for support, extra time during consultations, education on DR for HCPs and patients, and effective tools such as a feasible protocol can lead to more patients on biologic DR.